METODE SYSTEMATIC LITERATURE REVIEW UNTUK IDENTIFIKASI METODE PENGEMBANGAN SISTEM INFORMASI DI INDONESIA - Indah Widyah Ningsih; Deni Malik; Candra Hadi Utomo; Aswan Aswan; Fenty Fauziah (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Information system is a group of components that have a relationship in achieving a goal. Information system development has various methods. The methods commonly used in the development of information systems are structured methods and object-oriented methods. It is not yet known how many information systems have been developed by these methods. The purpose of this research is to identify information system development methods in Indonesia with data obtained from related articles throughout 2021 about information systems. This research uses the Systematic Literature Review (SLR) method. The SLR method is useful for identifying the development of information systems in Indonesia with certain relevant questions, using this method, a systematic review and identification of journal articles can be carried out with each process following predetermined stages. The results of this study, the structured method is the dominant method used in completing the development of information systems